Efficient Engraftment of Human Induced Pluripotent Stem Cell-Derived Hepatocyte-Like Cells in uPA/SCID Mice by Overexpression of FNK, a Bcl-xLMutant Gene. Issue 6 (June 2015) - Nagamoto, Yasuhito; Takayama, Kazuo; Tashiro, Katsuhisa; Tateno, Chise; Sakurai, Fuminori; Tachibana, Masashi; Kawabata, Kenji; Ikeda, Kazuo; Tanaka, Yasuhito; Mizuguchi, Hiroyuki
Human liver chimeric mice are expected to be applied for drug toxicity tests and human hepatitis virus research. Human induced pluripotent stem cell-derived hepatocyte-like cells (iPSC-HLCs) are a highly attractive donor source for the generation of human liver chimeric mice because they can be produced on a large scale and established from an individual. Although these cells have been successfully used to generate human liver chimeric mice, there is still room for improvement in the repopulation efficiency. To enhance the repopulation efficacy, the human iPSC-HLCs were transduced with an adenovirus vector (Ad-FNK) expressing FNK, a hyperactive mutant gene from Bcl-xL, which was expected to inhibit apoptosis in the process of integration into liver parenchyma. We then transplanted Ad-FNK-transduced human iPSC-HLCs into urokinase-type plasminogen activator-transgenic severe combined immunodeficiency (uPA/SCID) mice (FNK mice) and evaluated the repopulation efficacy. The antiapoptotic effects of the human iPSC-HLCs were enhanced by FNK overexpression in vitro. Human albumin levels in the transplanted mice were significantly increased by transplantation of Ad-FNK-transduced human iPSC-HLCs (about 24, 000 ng/ml). Immunohistochemical analysis with an anti-human αAT antibody revealed greater repopulation efficacy in the livers of FNK mice than control mice. Interestingly, the expression levels of human hepatocyte-related genes in the human iPSC-HLCs of FNK mice were much higher than those in the human iPSC-HLCs before transplantation. We succeeded in improving the repopulation efficacy of human liver chimeric mice generated by transplanting the Ad-FNK-transduced human iPSC-HLCs into uPA/SCID mice. Our method using ectopic expression of FNK was useful for generating human chimeric mice with high chimerism.